Association of atrial fibrillation burden and clinical profile with blood biomarkers: Results from the ISOLATION Ablation Cohort - Zarina Habibi, MD; Dominique V.M. Verhaert, MD, PhD; Konstanze Betz, MD; Ben J.M. Hermans, MD, PhD; Joris Winters, MD, PhD; Suzanne A.M. Philippens; Sevasti-Maria Chaldoupi, MD, PhD; Bart Maesen, MD, PhD; Jos G. Maessen, MD, PhD; Aaron Isaacs, PhD; Sjoerd W. Westra, MD; Robin Nijveldt, MD, PhD; et al. (Heart Rhythm O2)
Background: Advances have been made in identifying biomarkers for atrial fibrillation (AF) outcomes. Objective: The link between clinical determinants, especially AF burden, and blood biomarkers remains underexplored. Methods: We conducted a cross-sectional analysis of AF patients scheduled for catheter ablation in the ISOLATION study (July 2020–May 2022, NCT04342312). Patient characteristics and blood samples were collected before ablation. AF burden was assessed using hand-held electrocardiograms (ECGs) over 4 weeks. Blood samples were analyzed for biomarkers, including bone morphogenetic protein 10 (BMP10), angiopoietin-2 (Ang-2), fibroblast growth factor 23 (FGF23), and others. We trained elastic net regression models to identify the most important clinical determinants out of 64 available clinical features. Results: We analyzed blood samples from 508 patients with a mean age of 63 ±9 years; 31.1% were female. Of these, 70% had paroxysmal AF and 30% persistent AF. Heart failure was present in 15% of patients. In 140 patients (28%), AF was observed during blood draw. AF burden before ablation was available in 389 patients. After multivariable analysis, the following clinical determinants were independently associated with biomarker levels: AF burden, AF during blood draw, age, heart failure, decreased kidney function, and female sex. Most notably, AF burden and AF rhythm at the time of sampling were strongly associated with various biomarker levels. Female sex was positively associated with BMP10 and FGF23, but negatively associated with high sensitive Troponin-T (hs-TNT). Conclusions: AF burden is a strong determinant of many biomarkers, underpinning their relevance as covariates in biomarker studies. Pro-fibrotic biomarkers are increased in female patients, whereas male patients more often show elevated biomarkers of myocardial injury.